Understanding the Use of Evacuation Routes as Earthquake and Tsunami Disaster Mitigation Education in Junior High Schools in Puring District - Sanyo Yoberta, Fidesia; Liesnoor Setyowati, Dewi; Budi Sanjoto, Tjaturahono (Jurnal Sains Sosio Humaniora, 2026)
This study aims to determine the level of understanding among public junior high school students in Puring District regarding the use of earthquake and tsunami evacuation routes, analyze the implementation of disaster mitigation education, and examine the influence of mitigation education on evacuation route comprehension. The study employs a quantitative approach. Data were collected through questionnaires distributed to public junior high school students in Puring District and analyzed using descriptive statistics and regression analysis. The results indicate that both the students' level of understanding regarding evacuation routes and the implementation of disaster mitigation education fall into the high category. Regression analysis reveals a significant positive influence of disaster mitigation education on understanding evacuation route usage, demonstrating that better educational implementation directly enhances student comprehension. Theoretically, these findings reinforce the framework of school-based risk reduction by highlighting educational intervention as a key driver of disaster readiness. Practically, this study emphasizes the need to strengthen disaster mitigation education by integrating disaster-related material into the curriculum, conducting periodic evacuation drills, and optimizing disaster management within schools. Furthermore, the study's findings serve as a basis for policymakers to develop comprehensive disaster mitigation education programs that align with the specific hazard characteristics of Puring District.